Early Childhood Education Under the NEP2020 Framework - Bansod, A. D. (Journal of Educational Research and Policies, 2025)
The early childhood education (ECE) is very important in shaping up the future of a child in later part of his education. The quality of education be imparted to every child will be similar if adequate importance and care be given at the nascent stage. Each toddler has the same right and privileges in getting the ensured quality education from their beginning of study. In India, though previous education policies gave some emphasis on preschool education, but it was not that systematic until a child attaints the formal schooling from standard one which entry level varies from 5years to 7 years state to state. The NEP2020 has in its policy document tried to unify the various preschool initiatives to a single umbrella. It has recommended that the formal schools will start their preschool activities for the child from three plus ages. The different kindergarten, Montessori's, aganwadis will function as per the formal schooling. One of the premier education board CBSE already implemented the scheme in tune with NEP2020, by opening balvatika. The entry age at standard one for all the child from the current academic session 2014 - 2015 is at least 6 years uniformly in all the states irrespective of their education boards. In my paper, why the maximum stress must be given at the formative stage of education has been discussed.